Common and not so Common Melanocytic Lesions in Children and Adolescents. (April 2018) - Yang, Chen; Gru, Alejandro A; Dehner, Louis P
The acquired melanocytic nevus is the most common lesion encountered by pediatric pathologists and dermatopathologists in their daily practice. In most cases, there are few difficulties in histopathologic diagnosis. However, it is the acquired melanocytic lesion known as the Spitz nevus, with its intrinsic atypical features which becomes the challenge since it exists along a histopathologic and biologic continuum from the atypical Spitz tumor to spitzoid melanoma. The frustration with some of these spitzoid lesions is that even the "experts" cannot agree as to the differentiation of one from the other even at the level of molecular genetics. Other melanocytic lesions are discussed including the congenital melanocytic nevus with its proliferative nodule(s) and melanoma as the ultimate complication. Although uncommon, cutaneous melanoma in the first 2 decades is emerging as a clinical problem especially in young women in the second decade of life. These are ultraviolet-associated neoplasms whose histopathologic and prognostic features are identical to the adult experience. Considerable progress has been made over the past 15 to 20 years in our understanding of cutaneous melanocytic lesions, but gaps still exist in the important group of spitzoid lesions. It can also be anticipated that more cutaneous melanomas in children will be seen in the future based upon epidemiologic studies.